Characterization of IXINITY® (Trenonacog Alfa), a Recombinant Factor IX with Primary Sequence Corresponding to the Threonine-148 Polymorph - Dougald M. Monroe; Richard J. Jenny; Kevin E. Van Cott; Shelly Buhay; Laura L. Saward (Advances in Hematology)
The goal of these studies was to extensively characterize the first recombinant FIX therapeutic corresponding to the threonine-148 (Thr-148) polymorph, IXINITY (trenonacog alfa [coagulation factor IX (recombinant)]). Gel electrophoresis, circular dichroism, and gel filtration were used to determine purity and confirm structure. Chromatographic and mass spectrometry techniques were used to identify and quantify posttranslational modifications. Activity was assessed as the ability to activate factor X (FX) both with and without factor VIIIa (FVIIIa) and in a standard clotting assay. All results were consistent across multiple lots. Trenonacog alfa migrated as a single band on Coomassie-stained gels; activity assays were normal and showed <0.002 IU of activated factor IX (FIXa) per IU of FIX. The molecule has >97%  γ-carboxylation and underwent the appropriate structural change upon binding calcium ions. Trenonacog alfa was activated normally with factor XIa (FXIa); once activated it bound to FVIIIa and FXa. When activated to FIXa, it was inhibited efficiently by antithrombin. Glycosylation patterns were similar to plasma-derived FIX with sialic acid content consistent with the literature reports of good pharmacokinetic performance. These studies have shown that trenonacog alfa is a highly pure product with a primary sequence and posttranslational modifications consistent with the common Thr-148 polymorphism of plasma-derived FIX.